Bibliotekų kaip viešojo sektoriaus institucijų veiklos vertinimo organizavimo galimybė viešojo administravimo požiūriu - Dvorak, Jaroslav; Rudžionienė, Jurgita (Information & Media, 2013)
Straipsnio tikslas – pažvelgti į bibliotekų, kaip viešojo sektoriaus institucijų, veiklos vertinimą viešojo administravimo požiūriu. Keliama sėkmingo bibliotekų veiklos vertinimo užtikrinimo problema. Bibliotekos, patirdamos spaudimą šiuolaikinėje konkurencinėje aplinkoje, privalo įgyvendinti priemones, užtikrinančias kokybišką jų veiklos rezultatą. Straipsnyje analizuojamas bibliotekos veiklos vertinimas kaip svarbi institucijos vadybos dalis viešojo administravimo požiūriu. Pateikiama vertinimo samprata, aptariama viešojo sektoriaus institucijų veiklos vertinimo specifika, vertinimo svarba bibliotekų sėkmingai plėtrai ir veiklumui užtikrinti. Išsamiai supažindinama su vertinimo funkcijomis, bibliotekų veiklos vertinimo lygmenimis, atskleidžiamos viešojo administravimo galimybės organizuojant bibliotekų veiklos vertinimą.Pagrindiniai žodžiai: veiklos vertinimas, viešasis administravimas, biblioteka.Feasibility to organize performance evaluation at a library as a public sector institution: public administration approachJaroslav Dvorak, Jurgita RudžionienėSummary The main issue of the article is the possibilities of performance evaluation in libraries as public sector institutions. The main task is to analyse the issue from the point of view of public administration. Such evaluation is analyzed in comparison with other instruments of public management (performance / internal audit, activity management). The main evaluation functions (improvement of strategic planning, accountability, knowledge production, marketing, community consolidation, enlightening and learning) are described. The present research emphasizes that evaluation users attempt to ensure several functions. The choice of the functions depends on the aim of the user of evaluation information, evaluation type or even the approaches of evaluation organization in the country. For assessing library performance, the four-level approach comprising the infrastructure of a library, its innovativeness, human resources, the quality of the place is presented. Valuing information, the information services as well as the overall public sector performance and its results are still challenging for libraries all over the world. Articulating and demonstrating the value and impact of information services in libraries as well as the whole library performance are still a major challenge for information management. It makes particular difficulties for developing an adequate institutional management and library administration. A lot of efforts to find the best ways for creating and implementing evaluation culture for information institutions, including libraries, are being made. Key words: performance evaluation, public administration, library.